Prenatal diagnosis of isolated inferior vena cava interruption with hemiazygos continuation – beware of association with dilated left innominate vein - Aborizk, Sameh (Prenatal Cardiology, 2024)
Herein, we present a case of isolated inferior vena cava (IVC) interruption with hemiazygos continuation filling into the left innominate vein. Such a condition raises suspicion of left isomerism, poses a risk of developing lower limb venous thromboembolism or sick sinus syndrome, and carries importance for future catheter assisted or surgical interventions.